Partnering With Patients to Conduct High‐Quality Research – Where Have We Been and Where Are We Going? - Whibley, Daniel; Merritt, Greg; Haymart, Megan; Piechowski, Patricia; Larkin, Knoll; Williams, David (Health Expectations, 2025)
The article discusses the 75th World Medical Association General Assembly's review of the Declaration of Helsinki, which emphasizes the necessity of patient involvement in all stages of medical research. Concurrently, the University of Michigan is developing the Patient Partners Academy (PPA) to foster collaborative partnerships between patients, caregivers, and academic researchers, supported by funding from the US National Institutes of Health. The PPA aims to create a curriculum that promotes co-creation of research, enhances patient confidence in participating in research processes, and addresses challenges such as tokenism and unclear roles for patient partners. Ultimately, the PPA seeks to transform patient-researcher collaborations into sustainable, meaningful partnerships that enhance the quality of clinical research.